サロマコ (エンスイコ) ニ オケル ice algae ニ ヨル チャクショク カイヒョウ - 星合, 孝男; ホシアイ, タカオ; 福地, 光男; フクチ, ミツオ; Hoshiai, Takao; Fukuchi, Mitsuo (1981)
P(論文) 北海道オホーツク海岸の紋別において, 流氷下端から, また, サロマ湖の湖氷下端からも, ice algaeによる着色層を見出した。サロマ湖は潟湖であり, 湖内には31‰以上の塩水が存在する。したがって, 例年1月から4月へかけて湖面を覆う氷は, 海氷と呼び得る性質のものである。サロマ湖北西岸トエトコにおける観察の結果, 冬季形成される海氷は, 20～40cmに達した後, ほとんど成長を止めることを知った。この時期, 海氷下に褐色層が形成され, Fragilariopsis, Nitzschia, Thalassiosiraなどの珪藻を主としたice algaeが認められた。クロロフィルaは25.88μg/lにも達した。南北両極海では, 海氷の下端付近でice algaeが繁殖し, 着色現象が起こることが広く知られている。昭和基地付近では, 2月中旬に結氷がはじまり, 3月, 海氷の厚さが30cmくらいになった後, 1ヵ月ほどその成長が停滞する。また, 冬期間, 1mを越すほどに成長した海氷は, 春10月以降ふたたび成長を止める。この二度の時期に, 珪藻を主としたice algaeの増加が海氷下面付近で起こる。北海道で見られたice algaeによる海氷の着色現象は, 昭和基地で秋季に見られた現象とよく似ている。サロマ湖においても, 昭和基地においても, 海氷下端でice algaeの繁殖が起こる時期には, 海氷下の海水中のクロロフィルa量は, それぞれ0.09-0.23μg/l, 0.05-0.13μg/lと低く, かつ減少傾向を示した。サロマ湖は, 海氷の着色が起こる, 北半球における最も南の地域に位置していると思われる。 The coloration of sea ice by the ice algae was studied at Mombetsu (44°20′N, 143°20′E) on the Okhotsk coast of Hokkaido and at Toetoko (44°11′N, 143°45′E) in a lagoon, Lake Saroma, which is also situated on the same coast, Hokkaido, Japan. Lake Saroma is usually covered with the ice between middle January and early April. A brown layer was found at the bottom of the sea ice in February from 1977 through 1980. The 1977's results showed that Fragilariopsis, Nitzschia, Thalassiosira and other pennate diatoms were dominant components of the ice algal community. Chlorophyll a and phaeopigment were detected from top to bottom of the sea ice of 20 to 40 cm thick and concentrated at the bottom part. The level of plant pigment concentration (25.88μg chl a/l) in the sea ice was higher than that of the sea water (0.09μg chl a/l). The increase of plant pigments with the lapse of time was observed, when the growth rate of the sea ice extremely decreased at ice thickness of 20 to 40cm. The present results agreed with the data obtained at Syowa Station, Antarctica, on the development of ice algal community. departmental bulletin paper